Analisis Pengaruh Ukuran Mata Pisau Serta Variasi Putaran Terhadap Kualitas Dan Kuantitas Pada Mesin Pencacah Daun - Sri Devi Marchelina Siahaan; Jhon Sufriadi Purba (PT. Padang Tekno Corp, 2024)
Processing leaves to make compost is generally still done by chopping using a machete, or many are not chopped, making it difficult for the leaves to decompose or rot. This research aims to determine the results of chopping using a single blade and by varying the size of the blade and varying the rotation speed of the machine. The benefit of this research is to determine the influence of leaf chopper machine components, especially the number of leaf chopper blades, using descriptive qualitative research methods with data collection methods, literature studies and observations. The research location is in the HKBP Nommensen University Laboratory workshop, Pematang Siantar, North Sumatra. The research process took the form of testing carried out in several stages, namely using a single blade by varying the length of the blade and varying the rotation speed of the machine to compare the speed and chopping results. Three trials were carried out each with varying blade lengths of 30cm, 35cm and 40cm and rotation variations of 2500rpm, 3000rpm and 5000rpm. The results are in the form of a comparison of speed and counting results between variations of 30cm, 35cm and 40cm. The test results more effectively lead to variations in blade size of 40cm. And the results of testing the engine rotation speed which is more effective leads to a rotation speed variation of 5000rpm.